Botulinum toxin treatment of synkinesia and hyperlacrimation after facial palsy. Issue 1 (1st July 1998) - Boroojerdi, B; Ferbert, A; Schwarz, M; Herath, H; Noth, J
Abstract : OBJECTIVES: To investigate the effects of injection of botulinum toxin type A (BTX A) into the orbicularis oculi muscle and lacrimal gland in patients with aberrant regeneration after facial palsy (facial synkinesias and hyperlacrimation). METHODS: The effect of the toxin injection (on average 75 mouse units of BTX A) into the orbicularis oculi muscle on facial synkinesias was assessed on a five point (0 to 4) scale in 10 patients with aberrant regeneration of facial nerve fibres after a peripheral facial nerve palsy. Six patients underwent a videographic control, which was assessed by a blinded independent investigator. In two patients with hyperlacrimation an extra dose of botulinum toxin (on average 20 mouse units BTX A) was injected into the lacrimal gland and the effect was assessed using the Schirmer test and on a three point scale. RESULTS: Botulinum toxin type A had a good to excellent (grades 3 and 4) effect over an average of six months after 91% of injections. In 9% the injections had a moderate (grade 2) effect. Patients with hyperlacrimation showed a nearly complete recovery. There were no systemic side effects but focal side effects due to a temporary weakness of the orbicularis oculi muscle were not uncommon. CONCLUSIONS: Botulinum toxin type A is the treatment of choice in motor and autonomic effects of aberrant regeneration of facial nerve after a peripheral palsy. The required dose is similar to or slightly lower than the dose usually recommended for hemifacial spasm.